International political economy : perspectives on global power and wealth - Frieden, Jeffry A.; Lake, David A. (London ; New York : Routledge, 2000)
Now in its fourth edition, this best-selling reader in international political economy offers 31 solid articles - 15 new - by renowned scholars in political science and economics.
1. Contending perspectives on international political economy -- 2. Historical perspectives -- 3. Production -- 4. Money and finance -- 5. Trade -- 6. Economies in development and transition -- 7. Current problems in international political economy.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: International economic relations; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Economics; International economic relations